Engineering amphiphilic alkenyl lipids for self-assembly in functional hybrid nanostructures - Raúl Gimeno-Ferrero; Victoria Valdivia; Inmaculada Fernández; María Luisa García-Martín; Manuel Pernia Leal (Scientific Reports)
Abstract The development of biocompatible hybrid nanosystems for advanced functional applications presents significant challenges to the research community. Key obstacles include the poor solubility of these nanosystems in water and the difficulty of precisely controlling their nanostructure dimensions and composition. A promising approach to overcoming these challenges is the self-assembly of surfactant-based building blocks into well-ordered hybrid nanostructures. In this study, we explore the relationship between structure and self-assembly in novel low molecular weight amphiphilic molecules to produce stable and biocompatible hybrid nanostructures. We investigated the self-assembly behavior of two families of amphiphiles derived from alkenyl lipids with one or two double bonds, leading to distinct hybrid supramolecular structures facilitated by the incorporation of hydrophobic iron oxide nanoparticles (IONPs) as templates. The presence of double bonds in the lipid tail and the morphology of the amphiphile influence the arrangement on the hydrophobic NPs. Amphiphiles with a single double bond in the lipid tail form highly water-soluble, well-ordered micellar-like structures on the IONP surfaces, while those with two double bonds create disordered lipid nanoparticles. Furthermore, these amphiphilic molecules can self-organize into higher-order hybrid supramolecular structures, such as vesicles, with potential applications in magnetic resonance imaging (MRI).